The Role of High Commision for Human Rights in the Protecting of Human Rights- An Analytical Study - Abdulrahman, Sahlaw Sabah; Hamasaeed, Prwsha Arkan (Journal of Legal and Political Studies, 2021)
In compliance with the demands of international conventions related to the protection of human rights by establishing national institutions for the protection of human rights, the Constitution of the Republic of Iraq of 2005 enacted the establishment of the High Commission for Human Rights as an independent body aimed at promoting and protecting human rights and protecting the rights and freedoms enacted in the constitution, the Law of the High Commission for Human Rights enacted the structure of the Commission and several specializations in order to achieve its objectives, the most prominent of which is coordination with the relevant authorities in preparing strategies and joint work mechanisms to ensure the achievement of their objectives, studying and evaluating legislation in force and submitting proposals and recommendations for Iraq's accession to international treaties and agreements related to human rights.and receiving complaints from individuals, groups and civil organizations about human rights violations and conducting investigations regarding them, and the commission has practiced these various competencies, but it is not at the required level, so the commission must strive seriously to reduce the daily violations of human rights in Iraq, by preparing more objective strategies and plans with the relevant authorities at the international and national levels.
Keywords: international conventions; human rights; Constitution of the Republic of Iraq; objective strategies; Commission for Human Rights